Distribution of Adiponectin Multimeric Forms In Chinese Women With Polycystic Ovary Syndrome and Their Relation To Insulin Resistance - Tao, Tao (2010)
OBJECTIVE: Adiponectin, an abundant adipokine with insulin sensitizing properties, exists different multimeric forms, including low molecular weight (LMW), medium molecular weight (MMW), and high molecular weight (HMW) species. Alterations in the distribution of adiponectin multimers and the relationship between adiponectin multimers and insulin resistance (IR) in women with the polycystic ovary syndrome (PCOS) remain unclear. To compare adiponectin multimerization status and estimate of insulin sensitivity in Chinese women with PCOS compared with age and body mass index (BMI)-matched controls. METHODS: Cross-sectional study involving 64 Chinese women with PCOS and 59 normal women. Circulating total adiponectin and its multimeric forms were determined by ELISA and insulin resistance was estimated using the homeostasis assessment insulin resistance index (HOMA-IR). RESULTS: After controlling for BMI status, levels of both total and HMW adiponectin were significantly lower in women with PCOS compared with normal women (P<0.05). Furthermore, HMW adiponectin provided a stronger contribution to models predicting insulin resistance than total adiponectin. Lastly, decreased HMW adiponectin was associated with increased HOMA-IR in both normal and PCOS women, and this association was independent of both overall adiposity and visceral adiposity. CONCLUSION: Levels of both total and HMW adiponectin are decreased in Chinese women with PCOS compared with normal control women and the differences in HMW adiponectin persists after controlling for BMI. Furthermore, HMW adiponectin is a stronger predictor of insulin resistance in both women with PCOS and normal women than total adiponectin.